A two-step procedure for Generating Domestic and Asymmetric International Trade Costs when Data are Scarce - Arman Mazhikeyev (University of Lincoln, Lincoln International Business School, Lincoln Economics and Finance Research Group (LEAF), 2019)
The practice of trade cost measurement faces several challenges related to data quality, methodology and theory; but the major issue is that of data scarcity. Due to these facts both domestic and asymmetric trade costs have been ignored despite being a feature of modern trade models. This paper offers a two-step procedure to tackle these limitations and fill the gaps between theory and p ractice. The results of this work show that domestic trade costs proportionally grow with economic size, and that international trade costs are highly asymmetric especially when trading pair sizes differ. Counterfactual simulation results that ignore domestic frictions and adopt symmetric international trade cost measures show over-predicted welfare and trade changes as a response to policy shock in larger sized countries rather than smaller countries. After the proper treatment of trade costs in the simulation, results improve.
Keywords: F13; F14; F21; F40; 330; trade costs; measurement; domestic frictions; asymmetric costs; international trade; gravity; trade policy simulations